If m(x) = x2 + 3 and n(x) = 5x + 9. which expression is equivalent to (mn)(x)?

L 3 If m(x) = x2 + 3 and n(x) = 5x + 9. which expression is equivalent to (mn)(x)? 5x3 + 9x2 + 15x + 27 25x2 + 90x + 84 X2 + 5x + 12 05x2 + 24 L 3 If m(x) = x2 + 3 and n(x) = 5x + 9. which expression is equivalent to (mn)(x)? 5×3 + 9×2 + 15x + 27 25×2 + 90x + 84 X2 + 5x + 12 05×2 + 24

A
THUMBS UP WILL BE REALLY APPRECIATED.
– UQHnias we have, mex) = x2+3 and m (2) = 5279 = (x) (w wil C (adu (redu (x2+3). (5249 יו X2 ( 5x+9) +3 ( 5x+ 9) 5×3+ 9×2 + 15% +27 (x) (en wil 5x349x24 158427
L 3 If m(x) = x2 + 3 and n(x) = 5x + 9. which expression is equivalent to (mn)(x)? 5x3 + 9x2 + 15x + 27 25x2 + 90x + 84 X2 + 5x + 12 05x2 + 24

Leave a Comment